Avaliação das ações de controle da transmissão vertical do HIV/AIDS entre puérperas atendidas em uma maternidade de Fortaleza-Ce - Barroso, Léa Maria Moura (2005)
The women in fertile age have been target of the contamination for the HIV, what it requires special attention, mainly in the gestation, therefore there is the risk of the vertical transmission (VT) of the HIV. The agreed therapy of high power showed decisive in the reduction of the VT tax, however the measures of control are not satisfactory. It was objectified to evaluate the actions of control the VT of the HIV in a public maternity. One is about research, descriptive, exploratory and avaliative type. For boarding of the study it was used complementation of the qualitative and quantitative research. The data were collected in Assis Chateaubriand School Maternity (MEAC), located in Fortaleza-Ceará, in period of September to December of 2004. The population’s study consisted of eight postpartum women with infection for the HIV and eight professionals who had given assistance to these postpartum women. The structuralized or standardized comment and the interview were used as techniques. As instruments for the data’s collection, a script of structuralized comment and a script of half-structuralized interview. The quantitative data had been analyzed and made use in figures; end the qualitative ones analyzed and organized through the proposal of content analysis. It obeyed the ethical aspects of the research with human beings and all the subjects had signed the term of free and clarified assent. The majority of postpartum women had between 22 and 29 years, was single, with steady union, and originating the country, there was low study, had between one and two children; it known of the diagnosis to less of one year, informed six or more prenatal’s consultations of and participated of specialized accompaniment. Little parcel of the pregnant initiated the antiretroviral therapy in the recommended period and to inform about partner’s serology. The maternity disposed the treatment for all the pregnant women at the moment of the childbirth work and in the childbirth. The majority of the health professionals that gave assistance was nurse, between 26 and 49 years and make reference at time of formation between one and nine years and of work in the maternity between one and 15 years; the minority received some type of training about VT. It was identified that professionals of health had left to realized advice and orientation about preparation of the infantile formula, foods and pursuing of the new-born, about puerperal consultation and adhesion to the treatment. The institution had insufficient amount of some resourchs and centered the fulfilling of the inquiry fiches. It was concluded that these results will guide in the planning of interventions for future actions, with sights to the improvement of the quality in the assistance to the pregnant women with HIV/aids. It is suggested creation of a organizacional and functional structure for the implementation of the protocol, qualifications, meetings of evaluation, responsible performance of the nurses, determination of attendance flow and elaboration of a manual directed to the professionals of health.